Pengetahuan Perawat Tentang Resusitasi Jantung Paru di Ruang Neonatus Rumah Sakit Umum Melati Perbaungan 2023 - Elpriska Elpriska (STIKES Columbia Asia Medan, 2024)
The resuscitation is an attempt to provide the oxygen the brain, heart and other important vital organs; through an action, which consist of heart massaging and guarantying the adequate of ventilation. Infant Mortality Rate (IMR) is amount of infant mortality under 1 year per 1000 alive-nativity. The highest cause of infant mortality and children under-five year is prenatal disturbs and respiration system sickness, low-weight of newborn infant (BBLR), asphyxia on newborn infant, stiff and squeezed breath. This research is intended to identify the nurse’s knowledge about the resuscitation of lung-heart on neonates that facing emergency respiration. The kind of used research is descriptive, both population and sample in this research are whole nurses who work in Neonates Room that are for 15 people, which taken by sampling total technique. The result of this reseach that obtained is wherein the nurse’s knowledge about the resuscitation of lung-heart, it is whose having good knowledge for 9 nurses (60%) and whose having sufficient knowledge is for 6 nurses (40%). It is can be concluded that nurse’s knowledge about the resuscitation of lung-heart in Neonates Room is good. It is expected for whole nurses in order to more increase their knowledge about the resuscitation of lung-heart, and be active in participating of resuscitation training for better. This reseach, on the other hand, may motivate the student nurses in increasing both their capability and knowledge about the resuscitatiion.